The Effect of Participation and Work Environment on Personnel Performance in the General Secretariat (Setum) of the Jakarta Metro Jaya Regional Police - Zulkifli Rangkuti; Rotunas Oktavian; Nurwulan Kusuma Devi (Dinasti International Journal of Digital Business Management, 2026)
The objectives of the study are as follows: to determine the effect of personnel participation on personnel performance, to determine the effect of the work environment on personnel performance, to analyze the effect of participation and the work environment simultaneously on personnel performance at the Setum Polda Metro Jaya. There is an effect of participation on employee work performance . This is proven by the results obtained. The calculated t value for the participation variable (X 1 ) is 7.606 while the t table value for n = 50 is 2.008 . So 7.606 > 2.008 , then H 0 is rejected and Ha is accepted, it can be stated that participation (X 1 ) has a significant effect on personnel performance (Y) . There is an influence of the work environment on employee work performance . Proven to be obtained The calculated t value for the work environment variable (X2 ) is 6.909, while the t table value for n = 50 is 2.008 . So 6.909 > 2.008, the Adjusted R Square value is 0.932 which shows that the Y variable (personnel performance) is influenced by the X1 variable ( participation ) and the X2 variable ( work environment ) by 93.2% and the remaining 6.8% is influenced by other factors not studied.